An Investigation on Eco Friendly Self-Compacting Concrete Using Spent Catalyst and Development of Structural Elements - Balamuralikrishnan R.; Ranya Al-Balushi; Asima Kaleem (Civil Engineering Journal, 2023)
The theme of this initiative is "Waste to Wealth." Construction materials, particularly concrete, need to have better qualities, including strength, rigidity, durability, and ductility, because Oman's construction industry is expanding. Self-compacting concrete (SCC) has more benefits than regular concrete, including better workability. The major focus of this study is the C30-grade SCC for the control mix, spent catalyst (zeolite catalyst)-based SCC, and the development of the RC beam's flexural behavior employing control and spent catalyst-based SCC. The preliminary study and the main study are the two study outcomes included in this project. Preliminary research involves creating four mixtures with various dosages of 3%, 6%, 9%, and 12% in order to optimize spent catalyst in C30 grade concrete. All of the cubes undergo a 28-day curing test. The cubes' compressive strength is tested in order to establish the ideal dosage, which is 9%. Develop a C30 grade control modified design mix in accordance with SCC and optimize chemical admixtures such as superplasticizer (SP) at different dosages, like 2, 2.5, 3, and 3.5%, using various trials and tests (slump flow, L-box, J-ring, V-funnel, and U-box tests), as well as the optimized dosage of spent catalyst (SC). The main study includes six singly reinforced RC beams with dimensions of 750 (L)×100 (B)×150 mm (D) that were cast and tested in the laboratory. After a 28-day curing period, two specimens were placed under a two-point loading setup, with the remaining two samples receiving the optimum dosages of spent catalyst and superplasticizer. All of the beams were tested using a Universal Testing Machine (UTM) with a 1000 kN capability. From the preliminary study, partial substitution of cement in control concrete of grade C30 using spent catalyst (SC), it was found that the 9% optimum dosage produces greater compressive strength compared to other doses, which are almost 10% rises at 28 days of curing period. Based on a different test, it was discovered that the optimum dose of 3% SP gave closer agreement and satisfied the need for SCC as per the BS standard. The load-carrying capability of the SCC beams is almost 21.7% higher than that of the control beams. Comparing the SCC beams to the control beams, their deflection was reduced by about 26% at the same load level, and their ductility rose by almost 33%. Comparatively to the control beam, the stiffness of 21.6% of SCC also rises. According to test results, the SCC beam performs better in every way when superplasticizer and spent catalyst are used at the recommended dosage. Doi: 10.28991/CEJ-2023-09-05-08 Full Text: PDF